Instructional Perspectives of YMCA Fitness Instructors - Christinia M. Scott (Adult Education Research Conference, 2023)
The study seeks to determine the amount of andragogical principles used by adult fitness instructors at the Greater Louisville YMCAs. The Modified Instructional Perspectives Inventory (MIPI) will measure the level of andragogical principles used by Greater Louisville YMCAs fitness instructors.
Keywords: Andragogy; Adult Education; Fitness Instructors; Modified Instructional Perspectives